Blending the real world and the virtual world: Exploring the role of flow in augmented reality experiences - Brannon Barhorst, Jennifer; McLean, Graeme; Shah, Esta; Mack, Rhonda (Journal of business research, 2021)
This study examines the ‘sweet spot’ of augmented reality (AR) through the lens of flow theory and has two primary objectives. First, the study seeks to determine whether investment in AR technologies is warranted by exploring flow in both an AR and a traditional shopping context. Second, the study examines the unique capabilities of AR to facilitate an enhanced state of flow and its positive influence across several consumer outcomes. To achieve these objectives, a commercially available AR app was utilized to conduct an online, between-subjects experiment with 500 participants. Partial least squares structural equation modeling was used to analyze the predictor variables of consumer flow, as well as the impact of flow across several consumer outcomes. Managerial and practical conclusions for marketers and designers are provided to supportthe creation and execution of AR technology within consumer contexts.